Transferring Shares to Employees or Directors: Exploring the Effect of Board Duality on Share Repurchase in Taiwan - Chen, Ni-Yun; Lee, Te-Kuan (Asian Journal of Business and Accounting, 2017)
Abstract This study investigates the possible wealth transfer from non-controlling shareholders to controlling shareholders through share repurchase in Taiwan. We examine two kinds of duality problems: Cases where top management including CEO concurrently serve as members of the board (board duality), and cases where chief executive officers concurrently serve as chairmen (CEO duality). We find that firms with duality problems are more likely to announce share repurchase with the purpose of transferring shares to employees and have lower cumulative abnormal returns surrounding the announcement. Further, the presence of independent directors mitigates the negative market reaction. Keywords: Corporate Governance, Share Repurchase, Board Duality, CEO Duality, Independent Directors